Influence of skate skiing without poles on trunk and lower extremity kinematics - Higginson, B. K.; Heil, D. P. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Skate skiing without the use of ski poles is a common training technique utilized by many skiers to improve skate skiing technique and performance. This training technique requires a greater focus on balance and stability throughout the stride cycle. This increased demand for balance and stability, as well as the loss of upper extremity contribution to forward propulsion, results in altered upper and lower body kinematics. This change in skate skiing kinematics has not been previously reported. Therefore, the purpose of this study is to quantify changes in upper and lower extremity kinematics while skate skiing with and without the use of ski poles.